(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This study compared principals’ management strategies for quality teaching and learning in public and private secondary schools in Enugu State. Three research questions guided the study and three null hypotheses were tested at 0.05 level of significance. The descriptive survey research design was adopted for the study. From a population of 25,579 a sample of 1,278 participants made up of 860 private and 418 public secondary schools teachers was drawn using multi-stage sampling procedure. A questionnaire titled “Principals’ Management Strategies Questionnaire (PMSQ) was used for data collection. The questionnaire was validated by three experts, two from Department of Educational Management and Policy and one from Department of Educational Foundations (Measurement and Evaluation) all in the Faculty of Education, Nnamdi Azikiwe University. Internal consistency coefficients of 0.82, 0.86 and 081 and 0.84 were obtained for the three sections of the questionnaire using Cronbach’s Alpha method. An overall reliability co-efficient of 0.83 was obtained for the entire questionnaire. Data were analyzed using mean for the research questions and t-test for the hypotheses. The p-value was used to determine the significance of difference at 0.05 significant level. The result among others revealed that both public and private secondary school principals adopt instructional leadership strategies, and decision making strategies for quality teaching and learning in secondary schools in Enugu State. Based on the findings, the study recommended among others that Private secondary school principals in Enugu State should be encouraged through workshops and seminars to emulate public secondary schools in adoption of instructional leadership strategies for quality teaching and learning. This will help them inculcate in teachers the needed skills, capacities and competences that will help them achieve instructional effectiveness